Inovasi Pemuda Tangguh dalam Digitalisasi: Membangun Kesadaran Kebangsaan di Era 5.0 yang Berkelanjutan - Fifi Arisanti Ocha (Universitas Negeri Surabaya, 2025)
This article discusses the role of youth innovation in utilizing digitalization to build national awareness in the sustainable 5.0 era. In the context of globalization and accelerating technology, it is crucial to integrate nationalism with digital advancements to strengthen national identity amidst the waves of change. The purpose of this study is to explore how youth-driven innovations can contribute to the enhancement of national awareness through the use of digital technology. The approach used in this study is a conceptual analysis with a descriptive-qualitative method, examining literature related to digitalization, youth innovation, and national awareness in the Industry 5.0 era. This study also highlights the role of digital platforms such as social media, community-based applications, and educational technologies in disseminating national values. The main findings show that innovative youth can act as agents of change by creating digital solutions that not only promote national awareness but also spread the spirit of unity and diversity in society. Innovations such as creative content that highlights local culture, educational applications about national history, and digital campaigns promoting active participation in national life are some concrete examples of these contributions. The implications of these findings suggest that the integration of youth innovation with digitalization holds great potential in creating a sustainable ecosystem that supports national awareness in the 5.0 era. The proper use of technology not only contributes to strengthening national identity but also to inclusive and sustainable social development. Therefore, support from various parties, including the government and educational institutions, is needed to continuously encourage youth involvement in digital innovation based on national values.